Impact of Parent Rock and Land Use on the Distribution and Enrichment of Soil Selenium in Typical Subtropical Karst Regions of Southwest China - Chunshan Xiao; Xing Xiong; Jianwei Bu; Zhongquan Hu; Jun Zhang; Chenzhou Yang; Yinhe Huang (Applied Sciences)
Selenium (Se) is essential for various metabolic and physiological functions in the human body. However, the mechanisms of Se cycling in soils, particularly under different parent materials and land uses, remain understudied. This study investigates the spatial distribution and influencing factors of total Se in surface soils derived from limestone and sandstone in paddy and dryland systems in a Se-rich karst region of Southwest China. The mean Se content was 0.5 mg/kg, with 100% of samples exceeding national and global background levels, confirming Zheng’an County as a newly recognized Se-rich area. Soil Se concentrations, along with environmental variables such as soil organic matter (SOM), pH, elevation, slope, and trace elements (V, Cr, and Zn), were analyzed. One-way ANOVA revealed significant differences in Se content between parent materials and land-use types. Stepwise multiple regression identified SOM as the strongest predictor of Se, while Spearman correlation showed significant associations with topographic and chemical factors. These findings highlight the complex interactions between geology, land use, and topography in Se dynamics. Given the global distribution of karst landscapes, this research provides valuable insights into Se behavior in similar environments worldwide, with implications for land management and nutritional security.